Le Canada et la Norvège au sein des enjeux arctiques. Une étude narrative et linguistique - Fjeldstad, Marte (The University of Bergen, 2016)
This study constitutes a comparative study of the Canadian and Norwegian Arctic strategy documents. The purpose of the study has been to examine how the Canadian and Norwegian governments present themselves as heroes" in their own Arctic narrative. To examine these White Papers two different theoretic approaches are used. A narrative approach helps us explore the White papers as a story, formed in five stages: the initial situation, the complication, the reaction, the resolution and the final situation. These stages establish the hypothesis and are tested based on the linguistic and text structural criteria. At the micro level, a subjectivity approach is used, to investigate lexical phenomena supporting the narrative hypothesis. The findings show that both the Canadian and the Norwegian government all in all appear to present themselves as heroes in their own Arctic story in very similar ways. Master i Fransk MAHF-FRAN FRAN350